2017
DOI: 10.1186/s12891-017-1550-0
|View full text |Cite
|
Sign up to set email alerts
|

No correlation between radiolucency and biomechanical stability of keeled and pegged glenoid components

Abstract: BackgroundThe purpose of this study was to examine biomechanical properties and the degree of radiolucency of two cemented basic glenoid designs for total shoulder arthroplasty. Our hypothesis was that a component with increased micro-motion in the laboratory at time zero would also exhibit a greater amount of radiolucency in patients at a minimum of 2 years post total shoulder arthroplasty.MethodsThirty cadaveric shoulders were divided into 2 groups (keel vs. peg). The glenoid components were first loaded wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…While increased translation may resemble native glenohumeral kinematics more accurately, [12,13] this may also lead to more eccentric loading on and greater micromotion of the glenoid component in the setting of TSA. As excessive micromotion of the glenoid component has been suggested as a signi cant risk factor for glenoid loosening in the long-term, [5,[32][33][34] these biomechanical time-zero ndings may be of clinical importance, alleviating concerns of implant loosening due to increased rocking motion.…”
Section: Discussionmentioning
confidence: 99%
“…While increased translation may resemble native glenohumeral kinematics more accurately, [12,13] this may also lead to more eccentric loading on and greater micromotion of the glenoid component in the setting of TSA. As excessive micromotion of the glenoid component has been suggested as a signi cant risk factor for glenoid loosening in the long-term, [5,[32][33][34] these biomechanical time-zero ndings may be of clinical importance, alleviating concerns of implant loosening due to increased rocking motion.…”
Section: Discussionmentioning
confidence: 99%
“…Eccentric loading along with the resulting rocking (micro) motion of the glenoid component has been identified as an important biomechanical factor for subsequent implant loosening, thus the glenoid design has usually been suggested to be essential for ensuring long-term stability and clinical survival [2][3][4]. Although biomechanical studies have shown that the glenoid design is critical for initial fixation strength [29], clinical and radiographic studies demonstrating the superiority of one design over another are yet to be reported [28,29]. More importantly, the inconsistency of clinical findings along with recent anatomic studies describing the humeral head to be rather elliptical in shape than a perfect sphere may imply that the design of the humeral head prosthesis may also have a considerable influence on the long-term stability of the glenoid component [8,11,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…To determine micro-motion of the glenoid component, four high-resolution differential variable reluctance transducer (DVRT) strain gauges (Microstrain, Burlington, VT, USA) were placed at the anterior, posterior, superior, and inferior aspect of the glenoid component (Fig. 2 ) [ 29 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations